2018
DOI: 10.1111/1460-6984.12407
|View full text |Cite
|
Sign up to set email alerts
|

Use of electropalatography in the treatment of speech disorders in children with Down syndrome: a randomized controlled trial

Abstract: EPG was an effective intervention tool for improving speech production in many participants. This may be because it capitalizes on the relative strength of visual over auditory processing in this client group. The findings would seem to warrant an increased focus on addressing speech production difficulties in current therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…To mitigate this, patients will be offered U-VBF at the completion of the study, if their speech errors remain. A previous study trialing a similar technology-based intervention with children with Down syndrome showed that no children were lost to follow-up in either arm of the trial when this was offered [21]. A further limitation of the current study, which cannot be completely mitigated, is a potential preference from the treating clinicians for one intervention over the other, in particular the trial intervention.…”
Section: Discussion and Summarymentioning
confidence: 85%
“…To mitigate this, patients will be offered U-VBF at the completion of the study, if their speech errors remain. A previous study trialing a similar technology-based intervention with children with Down syndrome showed that no children were lost to follow-up in either arm of the trial when this was offered [21]. A further limitation of the current study, which cannot be completely mitigated, is a potential preference from the treating clinicians for one intervention over the other, in particular the trial intervention.…”
Section: Discussion and Summarymentioning
confidence: 85%
“…To our knowledge, EMA has hence only been used with school-aged children (e.g., Terband, Maassen, Van Lieshout, & Nijland, 2011). Electropalatography (EPG) was more readily adapted to child speech research (e.g., Gibbon, Hardcastle, & Dent, 1995;Wood, Timmins, Wishart, Hardcastle, Cleland, 2019;Gibbon, 1999). Contrary to EMA, EPG estimates places of contact between the tongue and the hard palate (for a comparison between EMA and EPG methods across a single speech dataset produced by adults, see Kochetov, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Electropalatography, also referred to as EPG, is a technique that allows to record the positioning and timing of the contact made between the tongue and the hard palate during the production of speech. EPG is a technique widely use in treatment of articulation disorder in adult population, and there are many studies to evaluate its usefulness in children population [1,2]. A key aspect of EPG is the use of an artificial palate, which is a custom-made device used for collection of the data, which consists of a sequence of contacts (on/off) for a series of electrodes distributed over the palate [3].…”
Section: Introductionmentioning
confidence: 99%